PENGARUH PENGELUARAN PEMERINTAH, INVESTASI DAN TENAGA KERJA TERHADAP PERTUMBUHAN EKONOMI DI KOTA TOMOHON PERIODE 2012-2023 - Jesica Buolo; Josep Bintang Kalangi; Irawaty Masloman (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
Economic growth is a long-term economic problem, and is an important phenomenon experienced by the world lately. Economic growth, which is one of the main indicators in assessing the success of a country's development, not only reflects the increase in the total value of goods and services produced, but also illustrates the effectiveness of economic policies implemented by the government. This study aims to analyze the effect of government spending, investment and labor on economic growth in Tomohon City using time series data sourced from the Central Statistics Agency of Tomohon City. The analysis was carried out using multiple linear regression using Eviews 12 software. The results of the study show that partially or individually with the t-test, the government expenditure variable has a negative and significant effect, investment has a positive effect on economic growth in Tomohon City, while the labor variable has a negative effect on economic growth in Tomohon City. Simultaneously or together with the f test, it shows that government spending, investment and labor have an effect on economic growth in Tomohon City. The contribution given by the three independent variables to economic growth in Tomohon City (R Square) is 71.02%.